1986
DOI: 10.1111/j.1365-246x.1986.tb04373.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of random velocity functions on the travel times and amplitudes of seismic waves

Abstract: Comparisons of the results of the numerical experiments were made with a record section from a long-range refraction profile recorded in Saskatchewan in 1979 by the Canadian COCRUST group. A non-layered interpretation of the observations indicated that an rms velocity deviation of only 1 per cent at any depth and a correlation distance of 5 km were sufficient to explain the irregularities in the observations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1989
1989
2003
2003

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 5 publications
(4 reference statements)
1
17
0
Order By: Relevance
“…We have chosen to examine the resultant velocity profiles at two locations: 25 percent along the profile, or 24 km from each shot point. For each location, the uncertainties allow the velocity structure above 3 km depth to be fit equally well by a simple velocity increase with depth; this result is quite consistent with that of Ojo and Mereu (1986) who showed that apparently linear segments on traveltime curves might result from small random heterogeneities superposed on a linear velocity increase, particularly in the upper few km where crack closure might lead to a large velocity gradient. For the profile 24 km from SP 12 (Figure 4a), a layer of fairly constant velocity (4.31 km/s), which could have a slight velocity gradient, occurs from 3-6 km depth.…”
Section: General Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…We have chosen to examine the resultant velocity profiles at two locations: 25 percent along the profile, or 24 km from each shot point. For each location, the uncertainties allow the velocity structure above 3 km depth to be fit equally well by a simple velocity increase with depth; this result is quite consistent with that of Ojo and Mereu (1986) who showed that apparently linear segments on traveltime curves might result from small random heterogeneities superposed on a linear velocity increase, particularly in the upper few km where crack closure might lead to a large velocity gradient. For the profile 24 km from SP 12 (Figure 4a), a layer of fairly constant velocity (4.31 km/s), which could have a slight velocity gradient, occurs from 3-6 km depth.…”
Section: General Resultssupporting
confidence: 76%
“…Furthermore, a simple but realistic assumption about the distributions of the above errors is that these errors are normally distributed; the argument for this assumption is from the central limit theorem in probability theory (see the deterministic and indeterministic decomposition of Ojo and Mereu, 1986). Finally, we assume that the three different types of errors are independent; this is obviously an acceptable assumption.…”
Section: Modelingmentioning
confidence: 99%
See 2 more Smart Citations
“…On the contrary, trying to investigate the properties, such as velocities, of the Earth's interior under the simplified assumption that the real medium is homogeneous may lead to serious errors (Cerveny and Firbas, 1984;Ojo and Mereu, 1986). To obtain uncertainties in the results of seismic refraction prospecting, the principal errors (or uncertainties) need to be classified.…”
Section: Introductionmentioning
confidence: 99%